Safety of young children on motorized two-wheelers around the world: A review of the global epidemiological evidence. (March 2015) - Bhalla, Kavi; Mohan, Dinesh
Abstract The safety of children younger than 10 years on motorized two-wheeled vehicles (MTWs) in low- and middle-income countries receives substantial attention from global road safety advocates. However, there is little empirical evidence available to describe the magnitude of the problem. Therefore, we constructed a population-level database of road traffic injury statistics disaggregated by age (< 5, 5–9, 10 + years) and mode of transport. Our database included mortality data from 44 countries and 5 Indian cities, and hospital admissions from 17 countries. The MTW fleet in these settings ranged from 2% to 70% of all registered vehicles. We find that children under 5 years averaged 0.05% (SD 0.13%) of all road traffic deaths, and 5–9 year olds averaged 0.11% (SD 0.25%). Even in regions with high prevalence of MTWs, young children comprised at most 1.5% of all road traffic deaths and 5.8% of all MTW deaths. Young children were a slightly larger proportion of all road traffic deaths in countries where MTWs were more common. However, after adjusting for population age structure, this effect was no longer evident. The percentage of child road traffic injuries that are due to MTWs increased with increasing MTW use, but at a much lower rate. Our findings suggest that children may be at lower risk from MTW crashes than previously assumed, and certainly at a lower risk than as pedestrians. Further studies are needed to explain the underlying mechanisms that regulate risk of road users.